Henry Prather Fletcher papers - Fletcher, Henry Prather, 1873-1959.
Correspondence, letterbook, diary, speeches, articles, scrapbook, clippings, memorabilia, photographs, and other papers relating chiefly to Fletcher's career from his enlistment in the Rough Riders (the 1st Volunteer Cavalry, U.S. Army) during the Spanish-American War through his service as a special adviser to the U.S. secretary of state following World War II. Documents his diplomatic service in Havana, Cuba; Peking, China; Lisbon, Portugal; Santiago, Chile; Mexico City, Mexico; Brussels, Belgium; and Rome, Italy. Also documents Fletcher's term as U.S. under secretary of state, 1921-1922, and his participation in the fifth International American Conference in 1923, Santiago, Chile, and the sixth International American Conference in 1928, Havana, Cuba. Postwar correspondence pertains primarily to the Republican Party.
Correspondents include William Jennings Bryan, Calvin Coolidge, Joseph C. Grew, Warren G. Harding, Herbert Hoover, Edward Mandell House, Charles Evans Hughes, Frank B. Kellogg, Frank Knox, Alfred M. Landon, Robert Lansing, Henry Cabot Lodge, John Bassett Moore, Benito Mussolini, Franklin D. Roosevelt, Willard Dickerson Straight, Robert A. Taft, William H. Taft, and Fletcher's wife, Beatrice Bend Fletcher.
Diplomat.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Fletcher, Beatrice Bend, -- -1941 -- Correspondence; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Coolidge, Calvin, -- 1872-1933 -- Correspondence; Grew, Joseph C. -- 1880-1965 -- Correspondence; Harding, Warren G. -- 1865-1923 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; House, Edward Mandell, -- 1858-1938 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Kellogg, Frank B. -- 1856-1937 -- Correspondence; Knox, Frank, -- 1874-1944 -- Correspondence; Landon, Alfred M. -- 1887-1987 -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Moore, John Bassett, -- 1860-1947 -- Correspondence; Mussolini, Benito, -- 1883-1945 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Straight, Willard Dickerman, -- 1880-1918 -- Correspondence; Taft, Robert A. -- 1889-1953 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; United States. -- Army -- History -- Spanish-American War, 1898.; United States. -- Army. -- Volunteer Cavalry, 1st.; United States. -- Department of State; Republican Party (U.S. : 1854- ); Diplomatic and consular service, American; Pan-Americanism.; Reconstruction (1939-1951); Spanish-American War, 1898.; World War, 1939-1945.; Belgium -- Foreign relations -- United States; Chile -- Foreign relations -- United States; China -- Foreign relations -- United States; Cuba -- Foreign relations -- United States; Italy -- Foreign relations -- United States; Mexico -- Foreign relations -- United States; Portugal -- Foreign relations -- United States; United States -- Foreign relations -- 20th century; United States -- Foreign relations -- Belgium; United States -- Foreign relations -- Chile; United States -- Foreign relations -- China; United States -- Foreign relations -- Cuba; United States -- Foreign relations -- Italy; United States -- Foreign relations -- Mexico; United States -- Foreign relations -- Portugal; United States -- Politics and government -- 1945-; Diplomats